Catalytic and stoichiometric flavanone oxidation mediated by nonheme oxoiron(iv) complexes as flavone synthase mimics: kinetic, mechanistic and computational studies. Issue 41 (27th September 2018) - Turcas, Ramona; Kripli, Balázs; Attia, Amr A. A.; Lakk-Bogáth, Dóra; Speier, Gábor; Giorgi, Michel; Silaghi-Dumitrescu, Radu; Kaizer, József
Abstract : Stoichiometric and catalytic oxidation of flavanone by nonheme Fe(iv )O, and their Fe(ii ) precursors with m -CPBA, as flavone synthase mimics is investigated. Abstract : The present study describes the first example of the stoichiometric and catalytic oxidation of flavanone by synthetic nonheme oxoiron(iv ) complexes and their precursor iron(ii ) complexes with m -CPBA as the terminal oxidant. These models, including detailed kinetic, mechanistic and computational studies, may serve as the biomimics of flavone synthase (FS) enzymes.